Upaya Peningkatan Partisipasi Belajar Sejarah Menggunakan Model TGT Dengan Aplikasi Quizizz di SMAN 2 Pariaman - Siska Mutia Jasni; Hera Hastuti (Jurusan Sejarah FIS UNP, 2021)
This study aims to increase the participation in learning history of students in class XI IPS 3 at SMAN 2 Pariaman through the application of the Team Games Tournament (TGT) learning model with the Quizizz application for the 2021/2022 academic year. This research can be an input and inspiration for teachers using the Team Games Tournament (TGT) learning model with the Quizizz application in other classes. With the application of the Teams Games Tournament (TGT) learning model, it can increase student participation in learning, students remain active and participate in learning activities and can increase their potential. This research is a classroom action research (CAR) which is carried out in two cycles. The subjects in this study were students of class XI IPS 3 SMAN 2 Pariaman Academic Year 2021/2022 who found 17 students. Data was collected by observing student participation and documentation, while the instrument used in the study was a guideline for observing student learning participation. Data analysis was carried out by quantitative descriptive data analysis showing the emergence or participation of students in history learning. Based on the results of the study, it can be said that the application of the Team Games Tournament (TGT) learning model with the Quizizz application can increase the participation in learning history of students in class XI IPS 3 SMAN 2 Pariaman. This proves or is supported by research data that has increased in aspects of student learning participation, namely students listening to the material by the teacher, students asking the teacher about material that is not understood, students listening and obeying the rules of the game, participating in the Quizizz game, students learning with material sources from books and the internet, students answer questions on Quizizz, students discover in completing Quizizz games, students compete for scores, and the winning team receives a prize from the teacher.